2018
DOI: 10.1186/s13040-018-0163-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel joint analysis framework improves identification of differentially expressed genes in cross disease transcriptomic analysis

Abstract: MotivationDetecting differentially expressed (DE) genes between disease and normal control group is one of the most common analyses in genome-wide transcriptomic data. Since most studies don’t have a lot of samples, researchers have used meta-analysis to group different datasets for the same disease. Even then, in many cases the statistical power is still not enough. Taking into account the fact that many diseases share the same disease genes, it is desirable to design a statistical framework that can identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The joint analysis methods developed in other fields of omics data analysis have proven useful in increasing the identification power by borrowing information from other similar diseases (Chen X. et al, 2013; Chung et al, 2014; Wang et al, 2016; Lin et al, 2017). In our previous study, we also demonstrated that our joint analysis framework aiming at DE gene detection is more advantageous than single data set analysis and meta-analysis in both simulation studies and real data cases combining different similar disease data sets (Qin and Lu, 2018).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The joint analysis methods developed in other fields of omics data analysis have proven useful in increasing the identification power by borrowing information from other similar diseases (Chen X. et al, 2013; Chung et al, 2014; Wang et al, 2016; Lin et al, 2017). In our previous study, we also demonstrated that our joint analysis framework aiming at DE gene detection is more advantageous than single data set analysis and meta-analysis in both simulation studies and real data cases combining different similar disease data sets (Qin and Lu, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…In this model, Pr( D 1 …, D N ) and α = {α 1 ,α 2 , …α N } need to be estimated from the data. This is a typical mixture model problem, therefore an EM algorithm is implemented to obtain the maximum likelihood estimate of these parameters following the derivation in previous literature (Pounds and Morris, 2003; Qin and Lu, 2018). The details are described as follows:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational methods have found increased application in analyzing the complexities underlying experimental studies and have been used in diverse areas of biomedical and cancer research such as to investigate expression profiles [ 12 , 13 ] and genomic alterations [ 14 , 15 ]; the role in miRNA in tumor origin localization [ 16 , 17 ]; in human HCC [ 18 , 19 ]; in the prediction of disease and cancer genes [ 20 , 21 ]; and in cancer prognosis [ 22 , 23 ]. To study the possible causes of HCC, we investigated the transcriptome of HSV-tk mouse liver tissues with HCC and hepatitis using computational analysis of microarray data.…”
Section: Introductionmentioning
confidence: 99%